1963
DOI: 10.1088/0029-5515/3/2/002
|View full text |Cite
|
Sign up to set email alerts
|

An ultra-fast pinch experiment

Abstract: We have used a quartz tube 10.8 cm long, 2.8 cm in internal diameter and 1 mm in wall thickness and produced the pinch effect by current in an axial direction in pre-ionized plasma. Before the gas was ionized, a magnetic field in the axial direction was produced by external coils. The following magnitudes are typical: duration of pulse, 25 mμsec; potential difference between the electrodes, 20 kV; current through the tube, 30 kA; gas pressure before ionization 50 mtorr. Measurements were made of the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1965
1965
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In ultra-fast pinch experiments [18] Adlam et al observed broadening of the skin layer compared with the value given by expression (5.11) by a factor of 25 (n 0 ~2X10 1 5 cm" 3 , 6 exp = 0. 3 -0.…”
Section: Penetration Of a Low-frequency Electromagnetic Field Into A ...mentioning
confidence: 84%
“…In ultra-fast pinch experiments [18] Adlam et al observed broadening of the skin layer compared with the value given by expression (5.11) by a factor of 25 (n 0 ~2X10 1 5 cm" 3 , 6 exp = 0. 3 -0.…”
Section: Penetration Of a Low-frequency Electromagnetic Field Into A ...mentioning
confidence: 84%
“…To obtain a velocity of compression that will yield fusion temperatures, or to ohmically heat a Z-pinch column to fusion temperatures, an applied voltage of the order of 106 V and a current of 106 A is required. While early attempts were made by Heflinger & Leonard (1961) and by Adlam & Holmes (1963) based on a proposal of J. E. Allen & J. H. Adlam (private communication), it was not until the recent development of high voltage pulse technology and the speculation of large ion Larmor radius stabilization that a new approach to Z-pinches was possible.…”
Section: Z -Pinch (A) Generalmentioning
confidence: 99%
“…The explicit form of the integrals depends on the ratio of the cyclotron frequency to the collision frequency: (6) A similar calculation makes it possible to represent the heat flux density in the form (7) Formulas ( 4)- (7) form the basis for further consideration of the effect of charge and energy transfer of electrons on the nonlinear penetration of a heating pulse into plasma. 10 )) . 2…”
Section: Current and Heat Flux Densitymentioning
confidence: 99%
“…Therefore the initial conditions for Eqs. (10), (11) have the form (12) The boundary conditions are derived from the continuity conditions for the tangential field components at the layer boundaries. Taking into account the smallness of the displacement current the boundary conditions have the form: (13) According to Eqs.…”
Section: / ) E N Mmentioning
confidence: 99%
See 1 more Smart Citation